Late poor outcomes of Clostridioides difficile infections in oncological patients: A multicentre cohort study. Issue 4 (July 2023) - Calbo, Esther; Hernández, Sergi; Sopena, Nieves; Castellá, Laia; Lopez-Contreras, Joaquín; Cuquet, Jordi; López-Sánchez, Maria; Pérez, Rafel; Gudiol, Carlota; Coloma, Ana; Marimón, Mariló; Espinach, Joan; et al.
Background: Cancer has been associated with an increased risk of in-hospital mortality in CDI patients. However, data on delayed mortality in cancer patients with CDI are scarce. Aim/Objective: The aim of the present study was to compare outcomes between oncological patients and the general population with Clostridioides difficile infection (CDI) after 90 days of follow-up. Methods: A multicenter prospective cohort study was conducted in 28 hospitals participating in the VINCat program. Cases were all consecutive adult patients who met the case definition of CDI. Sociodemographic, clinical, and epidemiological variables and evolution at discharge and after 90 days were recorded for each case. Findings/results: The mortality rate was higher in oncological patients (OR = 1.70, 95% CI: 1.08–2.67). In addition, oncological patients receiving chemotherapy (CT) presented higher recurrence rates (18.5% vs 9.8%, p = 0.049). Among oncological patients treated with metronidazole, those with active CT showed a higher rate of recurrence (35.3% vs 8.0% p = 0.04). Discussion: Oncological patients presented a higher risk of poor outcomes after CDI. Their early and late mortality rates were higher than in the general population, and in parallel, those undergoing chemotherapy (especially those receiving metronidazole) had higher rates of recurrence